Pimobendan Inhibits HBV Transcription and Replication by Suppressing HBV Promoters Activity - Si-Yu Yuan; Hai-Bo Yu; Zhen Yang; Yi-Ping Qin; Ji-Hua Ren; Sheng-Tao Cheng; Fang Ren; Betty Yuen Kwan Law; Vincent Kam Wai Wong; Jerome P. L. Ng; Yu-Jiao Zhou; Xin He; et al. (Frontiers in Pharmacology, 2022)
Current anti-HBV therapeutic strategy relies on interferon and nucleos(t)ide-type drugs with the limitation of functional cure, inducing hepatitis B surface antigen (HBsAg) loss in very few patients. Notably, the level of HBsAg has been established as an accurate indicator to evaluate the drug efficacy and predict the disease prognosis, thus exploring a novel drug targeting HBsAg will be of great significance. Herein, by screening 978 compounds from an FDA-approved drug library and determining the inhibitory function of each drug on HBsAg level in HepG2.2.15 cells supernatant, we identified that pimobendan (Pim) has a powerful antiviral activity with relatively low cytotoxicity. The inhibitory effect of Pim on HBsAg as well as other HBV markers was validated in HBV-infected cell models and HBV-transgenic mice. Mechanistically, real-time PCR and dual-luciferase reporter assay were applied to identify the partial correlation of transcription factor CAAT enhancer-binding protein α (C/EBPα) with the cccDNA transcription regulated by Pim. This indicates Pim is an inhibitor of HBV transcription through suppressing HBV promoters to reduce HBV RNAs levels and HBsAg production. In conclusion, Pim was identified to be a transcription inhibitor of cccDNA, thereby inhibiting HBsAg and other HBV replicative intermediates both in vitro and in vivo. This report may provide a promising lead for the development of new anti-HBV agent.